توجهات السياسة الخارجية الألمانية بعد قيام الوحدة - د. أحمد باسل البياتي (PROSPECTIVE RESEARCHES, 2023)
The expanding policy the Nazist Germany and the international conflict between the previous soviet Union from on side and United states, Britain and France from the other after the II world war have the essential motive to divide Germany into two separate states lacking sovereign. The conflicating forties were not ready to UN. Germany again. But the political developments and sudden events occurred in Russia and eastern Europe, in addition to the American policy and the wise policy of the German politicians all have shared in the unity of Germany, this unity was not expected to be achieved so soon by many thinkers, politicians, and observers.